UK Diplomatic representation in Oman (1971)
Keywords: Relations -- Oman -- Royaume-Uni

Political relations between Oman and UK (1971)
This file relates to relations between the UK and Oman. It contains correspondence, briefs, and records of conversations concerning: The visit of the Sultan of Oman Qaboos Bin...
Keywords: Relations -- Oman -- Royaume-Uni

Political relations between Oman and UK (1971)
This file relates to relations between the UK and Oman, and in particular the replacement of D G Crawford as the Consul General in Muscat by D F Hawley. It includes...
Keywords: Relations -- Oman -- Royaume-Uni